Association of IL-1ra and adiponectin with C-peptide and remission in patients with type 1 diabetes - Pfleger, Christian; Mortensen, Henrik B; Hansen, Lars; Herder, Christian; Roep, Bart O; Hoey, Hillary; Aanstoot, Henk-Jan; Kocova, Mirjana; Schloot, Nanette C (American Diabetes Association, 2008)
We investigated the association of anti-inflammatory cytokine interleukin (IL)-1 receptor antagonist (IL-1ra), adiponectin, proinflammatory cytokines IL-1 beta, IL-6, and CCL2, and tumor necrosis factor-alpha with beta-cell function, metabolic status, and clinical remission in patients with recent-onset type 1 diabetes.